Recollections of an Irish Born Doctor in Nineteenth-Century Argentina. Ed. Susan Wilkinson - Barnwell, David (ABEI Journal, 2015)
Recollections of an Irish Born Doctor in Nineteenth-Century Argentina. Ed. Susan Wilkinson. Washington, England: The Memoir Club, 2015.